An approach for damage initiation and propagation in metal and carbon fiber hybrid composites manufactured by robotic fiber placement. (15th July 2021) - Ammar, Mohamed M.A.; Shirinzadeh, Bijan; Zhao, Pan; Shi, Yaoyao
Highlights: A novel failure approach for the steel/carbon fiber hybrid composites. Manufacturing new multifunction composites using the robotic fibre placement technique. Complete analysis of the material behavior under normal tensile loads. Predicting the damage propagation through FEA using a built-in software module. Abstract: Integrating the steel fibers into the carbon fiber-reinforced polymers (CFRP) structures provides a new material with unique properties, e.g., superior specific strength and stiffness, high damage tolerance, energy absorption and electrical functions. Manufacturing and investigating the steel/carbon fiber reinforced polymers (SCFRP) are an important attempt to monopolize their potential to contribute to the aviation industry. The current study presents a novel failure approach which can predict the damage initiation and propagation inside the metal/carbon hybrid composites. The analytical formulation is developed and implemented on the material through finite element analysis (FEA). Different SCFRP specimens are fabricated according to the required specifications using the robotic fiber placement (RFP) process. Subsequently, the failure behavior is analyzed by applying the tensile tests on the specimens. The analytical results are compared and validated by the experimental data. The proposed approach would enable predicting the failure behavior and the stiffness degradation of the generated material.